An examination of historical control histopathology metadata from 51 Amphibian Metamorphosis Assays. (21st October 2021) - Wolf, Jeffrey C.; Bejarano, Adriana C.; Fort, Douglas J.; Wheeler, James R.
Abstract: The Amphibian Metamorphosis Assay (AMA) is used to identify substances that potentially interfere with the normal function of the hypothalamic-pituitary-thyroid (HPT) axis. Although numerous AMA studies have been performed since the establishment of this assay a decade earlier, a comprehensive, large-scale examination of histopathology data obtained from control larvae has not been performed. The current investigation reviewed 51 AMA experiments conducted at 7 different laboratories in Europe and North America. Dilution water control and/or solvent control specimens from each study (1, 335 animals total) had been evaluated microscopically by one of eight anatomic pathologists. In order of descending frequency, the most common findings in prometamorphic Xenopus laevis controls were the core criteria of follicular cell (FC) hypertrophy, FC hyperplasia, thyroid hypertrophy, and thyroid atrophy, respectively. Less frequently recorded were non-core and ad hoc diagnoses, the toxicological relevance and utility of which were in some cases uncertain. As anticipated, the prevalence of FC hypertrophy and FC hyperplasia diagnoses were at least partially dependent on the Nieuwkoop and Faber (NF) stage at sacrifice. The recorded frequencies of each of the four core diagnoses also differed according to pathologist, which suggests that pathologist diagnostic interpretation is a potential source of variability across AMA study outcomes. Based on the current examination of the AMA historical data, and further hands-on experience with this assay, diagnostic approaches to evaluating the histopathology endpoint are discussed, and several recommendations are proposed for the refinement of core diagnostic criteria assessment.